2020
DOI: 10.1007/s12192-020-01092-2
|View full text |Cite
|
Sign up to set email alerts
|

Peeking from behind the veil of enigma: emerging insights on small heat shock protein structure and function

Abstract: This is a short paper on new ways to think about the structure and function of small heat shock proteins (sHSPs), perhaps the most enigmatic family among protein chaperones. The goal is to incorporate new observations regarding the disordered regions of small heat shock proteins (sHSPs) into the large body of structural information on the conserved structural alpha-crystallin domains (ACD) that define the sHSP family. Disordered regions (N-terminal region and C-terminal region or NTR and CTR, respectively) rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 12 publications
(21 reference statements)
0
25
0
Order By: Relevance
“…The available structures indicate that the key to overall structural flexibility might be envisioned in the variability of the contacts formed by three sequence parts (NTR, ACD, CTR). This is further supported by progress in understanding the structure functional relationship of some other human sHsps ( Figure 3 ) [ 63 , 64 , 66 , 145 ].…”
Section: The Structure Of Human Shspsmentioning
confidence: 80%
See 2 more Smart Citations
“…The available structures indicate that the key to overall structural flexibility might be envisioned in the variability of the contacts formed by three sequence parts (NTR, ACD, CTR). This is further supported by progress in understanding the structure functional relationship of some other human sHsps ( Figure 3 ) [ 63 , 64 , 66 , 145 ].…”
Section: The Structure Of Human Shspsmentioning
confidence: 80%
“…Additionally, a conserved sequence stretch of one of the Hsp20 NTRs (residues 27-RLFDQRFG-34; [ 63 , 90 ]) binds to a groove formed on the ACD dimer (β3/β3), which represents a similar structural arrangement as observed for the NTR-ACD contacts in the HspB2-HspB3 hetero-oligomer [ 64 ]. Interestingly, the two NTRs of pHsp20 display different arrangements, again highlighting the structural flexibility modulating the contacts formed and once more defining the NTR as key player for structural variability ( Figure 3 C) [ 17 , 82 , 145 ]. Several grooves on the ACD additionally provide the necessary, suitable contact sides for the NTR, presumably allowing the variability in oligomer formation [ 64 , 145 ].…”
Section: The Structure Of Human Shspsmentioning
confidence: 99%
See 1 more Smart Citation
“…Oversimplifying, we can suppose that HspB1 and HspB5 have three, whereas HspB6 and HspB8 have only two potential sites involved in heterooligomerization. It was suggested that conserved (S/G)RLFD pentapeptide could interact with ACD [41] and by this means drive the interaction of different sHsps. In the case of HspB1 and HspB5, the mutation or deletion of this pentapeptide in either HspB1 or HspB5 will decrease the number of potential binding sites from six (three on HspB1 and three on HspB5) to five.…”
Section: Discussionmentioning
confidence: 99%
“…The ACD is thought to be essential for the dimerization and function of sHSPs [5]. The NTR is generally hydrophobic [6] and involved in oligomer formation of sHSPs and the interaction with substrate proteins [7]. The CTR is polar, flexible, and plays a key role in the stability and assembly of oligomers [8].…”
Section: Small Heat Shock Proteins (Shsps)mentioning
confidence: 99%